Financial and Monetary Policy of Great Britain During the Napoleonic Wars - Silberling, Norman J. (Quarterly Journal of Economics, 1924)
The sources of revenue; how much from loans, how much from taxes, 216. — Comparison with the World War, 219. — Relation of unfunded loans to total borrowing, 220. — Remittances to foreign countries: the machinery of payment, 222. — Total of loans and subsidies, 225. — Import and export statistics unattainable, 229.